Serum immunoglobulin from Nellore cattle produced by in vitro fertilization and treated for umbilical diseases - Rodrigues, Celso Antonio [UNESP]; Santos, Paulo Sergio P. [UNESP]; Feitosa, Francisco Leydson F. [UNESP]; Perri, Sílvia Helena V. [UNESP]; Lisboa, Júlio Augusto N.; Teodoro, Piero Henrique M. [UNESP]; de Araújo, Marcelo Augusto; Filho, Mário Nelson Viana [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to measure serum immunoglobulin concentrations of Nellore cattle produced by in vitro fertilization (IVF) with umbilical diseases and to evaluate surgical excision as a method of treatment. Sixteen cattle with ages ranging from 1 to 15 months, males and females, affected by umbilical diseases were enrolled in the study. Blood samples were collected for cell counts and the determination of immunoglobulin concentrations by electrophoresis and zinc sulphate turbidimetry (ZST). Four calves were presented with umbilical herniation, two with an umbilical herniation associated with a persistent urachus, two with an umbilical herniation with a persistent urachus and omphaloarteritis, three with an umbilical herniation and an urachal diverticulum, three with a persistent urachus, one with an urachal diverticulum, and one with omphalitis. The blood cell counts pre- and post-surgical revealed differences in cell volume and the number of leukocytes. The immunoglobulin values measured by electrophoresis values were below normal in most animals, whereas the ZST showed normal levels in most of them. Most of the calves affected by umbilical diseases and produced by IVF presented hypoglobulinaemia. Correlations between umbilical diseases, failure of passive transfer of immunity and IVF could not be demonstrated.
Keywords: Calves; Clinics; Failure of passive transfer of immunity; In vitro fertilization; Omphalitis; Persistent urachus